3D PRINTING IN THE FASHION INDUSTRIES AND ITS INFLUENCE ON SUPPLY CHAIN MANAGEMENT (Вестник университета)
Use of modern innovative technologies calls into question rationality of use of a traditional chain of deliveries in which proceeding from the principle of economy at the expense of scale, production is carried out centrally and further nished products are delivered to the di erent countries of the world. It, in turn, can lead to cancellation of a tendency of the globalization characteristic in the last several decades of various industries. Such tendency fully belongs to the fashion industry, that is to that sector of economy in which the clothes, footwear, accessories are made. In article the investigation considering in uence of modern innovative technologies including the 3D printing on management of chains of deliveries to the fashion industries is made.